PELATIHAN PENGGUNAAN APLIKASI PENGARSIPAN SURAT PERTANAHAN PADA DINAS PERTAHANAN DAN TATA RUANG DAERAH ISTEMEWA YOGYAKARTA - Elsafira Budi Dewantari; Trisa Ayunanda Saputri; Shofi Putri Ekadewi; Rabiatul Adawiyah; Yuli Astuti; Acihmah Sidauruk; Erni Seniwati (Batara Wisnu : Indonesian Journal of Community Services, 2023)
A website-based archiving information system is an application that allows users to manage digital documents in a structured and easily accessible manner via the internet. In today's digital era, the use of digital documents is increasing and requires a filing system that can store, manage, and provide document access easily and quickly. Therefore, the use of a website-based archiving information system is becoming increasingly popular because it makes it easy to manage digital documents. A web-based archiving information system consists of several features that allow users to manage documents easily. These features include document search, document upload, and document categories. In the document search feature, users can easily search for documents by entering specific keywords. The document upload feature allows users to upload documents to the system easily and quickly. The document categories feature allows users to group documents according to specific types or categories. The design of this archiving information system website is created using Laravel. The result of this research is the Surat Dinas Archiving Information System at the Land and Regional Planning Agency of the Special Region of Yogyakarta.